State of Research on the History of Football in Kielce Province in the Years 1919–1939 - Krzysztof Kościański (Sport i Turystyka)
The following article presents the state of research on the history of football in Kielce province in the years 1919–1939. During the discussed period, football in the province of Kielce developed in four centres: Częstochowa, Kielce, Radom and the Dąbrowa Basin (Zagłębie Dąbrowskie). Researchers who addressed the issue of football in the interwar period in these regions were: Adam Fryc (the Dąbrowa Basin), Paweł Jończyk (the Dąbrowa Basin), Krzysztof Kościański (Częstochowa), Eligiusz Małolepszy (Częstochowa), Marek Michnik (Kielce), Zbigniew Moskwa (Kielce), Lech Mosiołek (Radom), Antoni Pawłowski (Kielce), Szymon Piasta (Kielce), Mirosław Ponczek (the Dąbrowa Basin). The state of research is supplemented by few monographs of sports clubs from the province of Kielce and studies on the history of football in Poland. A significant part of the publications is of a popular science nature. They lack source footnotes and bibliography. As regards the state of research on the history of football in the province of Kielce in the years 1919– 1939, no comprehensive work covering this topic has been published so far.